Cross-channel Marketing Integration: Measuring its Impact on Brand Perception and Sales - Purwoko, Bambang (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Multichannel marketing integration is an important strategy in modern marketing that influences customer loyalty and brand perception. In this literature review, researchers explore the impact of multichannel marketing integration on long-term customer loyalty and positive brand perceptions. The research results show that the quality of multichannel marketing integration contributes significantly to customer engagement and improved brand perception. However, challenges such as brand message consistency and technology investments can hinder smooth implementation. The implications of this research highlight the importance of overcoming these barriers to maximize the benefits of multichannel marketing integration. These findings provide valuable insights for marketing practitioners in developing effective strategies to increase customer loyalty and brand perception in an increasingly complex business environment.